Molecular Detection of Reticuloendotheliosis Virus 5′ Long Terminal Repeat Integration in the Genome of Avipoxvirus Field Strains from Different Avian Species in Egypt - Samah M. Mosad; Mohamed El-Tholoth; Ali A. El-Kenawy; Lina Jamil M. Abdel-Hafez; Fatma A. El-Gohary; Hanem El-Sharkawy; Mona Mohieldin Elsayed; Ayman A. Saleh; Ehab Kotb Elmahallawy (Biology, 2020)
Avipoxviruses (APVs) are among the most complex viruses that infect a wide range of birds’ species. The infection by APVs is often associated with breathing and swallowing difficulties, reduced growth, decreased egg production, and high mortalities in domestic poultry. In the present study, 200 cutaneous nodular samples were collected from different avian species (chicken, pigeon, turkey, and canary) suspected to be infected with APVs from Dakahlia Governorate, Egypt. Pooled samples (n = 40) were prepared and inoculated in embryonated chicken eggs (ECEs). APVs were then identified by polymerase chain reaction (PCR) and sequence analysis of the APV P4b gene. Furthermore, the forty strains of APVs were screened for the presence of reticuloendotheliosis virus (REV)-5′LTR in their genomes. Interestingly, the phylogenic tree of the APV P4b gene was separated into 2 clades: clade 1, in which our fowlpox virus (FWPV), turkeypox virus (TKPV), and canarypox virus (CNPV) isolates were grouped, along with reference FWPVs and TKPVs retrieved from GenBank, whereas, in clade2, the pigeonpox virus (PGPV) isolate was grouped with PGPVs retrieved from GenBank. Likewise, REV-5′LTR was amplified from 30 strains isolated from chicken, turkey, and canary, while PGPV strains were free from REV-5′LTR integration. To the best of our knowledge, this study involved the detection and characterization of REV-5′LTR insertions in the APVs field isolates in Egypt for the first time. Given the above information, further future research seems recommended to understand the impact of the resulting REV-5′LTR insertions on the pathogenesis, virulence, and inadequate vaccine protection against APVs.